Pan-African polyspecific antivenom produced by caprylic acid purification of horse IgG: an alternative to the antivenom crisis in Africa. - Gutiérrez, J; Rojas, E; Quesada, L; León, G; Núñez, J; Laing, G; Sasa, M; Renjifo, J; Nasidi, A; Warrell, D; Theakston, R; Rojas, G (2005)
A polyspecific Pan-African antivenom has been produced from the plasma of horses immunized with a mixture of the venoms of Echis ocellatus, Bitis arietans and Naja nigricollis, the three most medically important snakes in sub-Saharan Africa. The antivenom is a whole IgG preparation, obtained by caprylic acid precipitation of non-IgG plasma proteins. The antivenom effectively neutralizes the most important toxic activities of the three venoms used in the immunization in standard assays involving preincubation of venom and antivenom before testing. This antivenom compares favourably with other antivenoms designed for use in Africa with respect to neutralization of the toxins present in the venom of E. ocellatus. Caprylic acid fractionation of horse hyperimmune plasma is a simple, convenient and cheap protocol for the manufacture of high quality whole IgG antivenoms. It constitutes a potentially valuable technology for the alleviation of the critical shortage of antivenom in Africa.